The Naturalist and his 'Beautiful Islands' Charles Morris Woodford in the Western Pacific - Russell Lawrence, David (ANU Press, 2014)
This book is a study of Woodford, the man, and what drove his desire to establish a colonial protectorate in the Solomon Islands. In doing so, it also addresses ongoing issues: not so much why the independent state broke down, but how imperfectly it was put together in the first place.